Determination of Direct and Indirect Effects on Milk Yield of Anatolian Buffaloes Using Path Analysis - Şahin, A; Aksoy, Y; Yildirim, A; Ulutaş, Z (Journal of the Hellenic Veterinary Medical Society, 2023)
This study aimed to determine the direct and indirect effects of the independent variables presented by the lactation lenght (LL), age of calving (CAGE), and daily milk yield (DMY) on the dependent variable of lactation milk yield (LMY) in Anatolian buffaloes. In this study, a total of 3761 LMY records of the 834 Anatolian buffaloes calving between 2012 and 2017 in Tokat province and around were used as the research material. In the study, the simple correlation coefficients between the dependent variable of LMY and independent variables were determined positive and significant (P<0.001). The research specified the direct determination coefficients of the independent variables of the LL, CAGE, and DMY on the dependent variable of LMY as 0.378, 0.004, and 0.350, respectively. The path coefficients related to LL, CAGE, and DMY were determined as 0.615, 0.021, and 0.592, respectively. Since the DMY and LL examined in the study had a high direct impact on the lactation milk yield, therefore it could be suggested that using these data as criteria in breeding programs conducted in the herds evaluated in the study will increase the success in the selections applied.